Complications of pupil expansion devices: a large real-world study - Yahalomi, Tal; Elhaddad, Omar; Avadhanam, Venkata; Tole, Derek; Darcy, Kieran; Levinger, Eliya; Tuuminen, Raimo; Achiron, Asaf (Frontiers in Ophthalmology, 2023)
Purpose: To assess the risk for uveitis, pseudophakic cystoid macular edema (PCME), and posterior capsular opacification (PCO) associated with the use of pupil expansion devices in cataract surgery. Design: A retrospective comparative cohort study. Participants: Patients who underwent routine cataract surgery with and without pupil expansion devices at the Department of Ophthalmology, Bristol Eye Hospital, UK, between January 2008 and December 2017. Methods: This study included 39,460 eyes operated without a pupil expansion device and 699 eyes operated with the device. Odds ratios for uveitis and PCME when using a pupil expansion device were calculated using univariate and multivariate regression analysis, having age, gender, diabetes, pseudoexfoliation, and pupil expansion device as independent variables. Multivariate Cox regression controlling for age and gender was used to estimate hazard ratios (HR) for Nd:YAG laser capsulotomies. Results: Postoperative uveitis and PCME were reported in 3.9% and 2.7% of the eyes operated with a pupil expansion device compared to 2.3% and 1.3% operated without the device (p=0.005 and p=0.002, respectively). In univariate regression analysis, eyes with pupil expansion devices showed a higher risk of postoperative uveitis or PMCE after cataract surgery (OR 1.88, 95%CI 1.39-2.55, p<0.001). In multivariate regression analysis, the risk for PMCE was greater among diabetic patients and in eyes with a pupil expansion device than in those without (OR 1.50, 95%CI 1.24-1.83, P<0.001; OR 1.90, 95%CI 1.16-3.11, P=0.01). In Cox regression analysis adjusted for the patient's age and gender, the use of a pupil expansion device was associated with higher Nd:YAG laser capsulotomy rates (HR 1.316, 95%CI 1.011-1.714, P=0.041). Conclusions: In our large cohort study, the use of pupil expansion devices in cataract surgery was associated with an increased risk of major postoperative complications. Effective anti-inflammatory treatment and follow-up are warranted in eyes operated with a pupil expansion device.